Asymptomatic carriers of Plasmodium spp. as infection source for malaria vector mosquitoes in the Brazilian Amazon - Alves, Fabiana Piovesan; Gil, Luiz Herman S.; Marrelli, Mauro T.; Ribolla, Paulo E. M. [UNESP]; Camargo, Erney P.; Da Silva, Luiz Hildebrando Pereira (My University, 2005)
We have described the existence of asymptomatic carriers of Plasmodium vivax and Plasmodium falciparum infections in native Amazon populations. Most of them had low parasitemias, detected only by polymerase chain reaction (PCR). Because they remain symptomless and untreated, we wanted to determine whether they could infect Anopheles darlingi Root, the main Brazilian vector, and act as disease reservoirs. Fifteen adult asymptomatic patients (PCR positive only) were selected, and experimental infections of mosquitoes were performed by direct feeding and by a membrane-feeding system. Seventeen adult symptomatic patients with high parasitemias were used as controls. We found an infection rate in An. darlingi of 1.2% for the asymptomatic carriers and 22% for the symptomatic carriers. Although the asymptomatic group infected mosquitoes at a much lower rate, these patients remain infective longer than treated, symptomatic patients. Also, the prevalence of asymptomatic infections is 4 to 5 times higher than symptomatic infections among natives. These results have implications for the malaria control program in Brazil, which focuses essentially on the treatment of symptomatic patients. © 2005 Entomological Society of America.
Keywords: Anopheles darlingi; Asymptomatic infection; Malaria; Mosquito feeding; animal; Anopheles; Brazil; comparative study; disease carrier; disease transmission; genetics; human; malaria; parasitology; Plasmodium; polymerase chain reaction; species difference; Animals; Disease Reservoirs; Humans; Insect Vectors; Polymerase Chain Reaction; Species Specificity; Plasmodium falciparum; Plasmodium vivax